2020
DOI: 10.1029/2020gl089427
|View full text |Cite
|
Sign up to set email alerts
|

A Satellite‐Detected Terrestrial Gamma Ray Flash Produced by a Cloud‐to‐Ground Lightning Leader

Abstract: We report measurements of a terrestrial gamma ray flash (TGF) detected by the Fermi Gamma‐ray Burst Monitor that was produced during a negative cloud‐to‐ground (CG) lightning leader. This is the first report of a downward directed TGF occurring during a CG flash but detected by a space‐based instrument. The gamma ray photons are produced 3 ms preceding a return stroke (−146 kA) and are essentially simultaneous with an isolated low frequency radio pulse. Based on timing, the pulse is estimated to initiate at ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Partially improving the detectability, the average gamma-ray energy is higher and the beam narrower (Ortberg et al, 2020). The positron-beam TGF detected by Fermi GBM is consistent with these predictions: The TGF was at the detection threshold of GBM, had a high-energy gamma ray (>10 MeV) and was observed at the low offset of 117 km (Pu et al, 2020). The TGF from the volcanic lightning was at the very large offset of ∼700 km and had a spectrum consistent with gamma rays Compton scattered from the primary beam.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Partially improving the detectability, the average gamma-ray energy is higher and the beam narrower (Ortberg et al, 2020). The positron-beam TGF detected by Fermi GBM is consistent with these predictions: The TGF was at the detection threshold of GBM, had a high-energy gamma ray (>10 MeV) and was observed at the low offset of 117 km (Pu et al, 2020). The TGF from the volcanic lightning was at the very large offset of ∼700 km and had a spectrum consistent with gamma rays Compton scattered from the primary beam.…”
Section: Discussionsupporting
confidence: 73%
“…In this case, the GBM observation would be of gamma rays produced by the reverse positron beam. Positron beams have been observed from below an upward‐directed TGFs (Bowers et al., 2018) and from space from a downward‐directed TGF (Pu et al., 2020). The reverse positron beam is expected to be ∼100 times weaker than the electron beam, reducing its detectability.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that TGFs are usually associated with upward negative leaders in intracloud flashes (Cummer et al, 2015;Lu et al, 2010). Pu et al (2020) also reported a downward TGF produced during a downward negative leader preceding a negative return stroke. We have demonstrated that these strong negative return strokes are preceded by a fast and powerful downward negative leader.…”
Section: Discussionmentioning
confidence: 88%
“…Pu et al. (2020) also reported a downward TGF produced during a downward negative leader preceding a negative return stroke. We have demonstrated that these strong negative return strokes are preceded by a fast and powerful downward negative leader.…”
Section: Discussionmentioning
confidence: 94%
“…Using a timing alignment procedure detailed in Pu et al (2019) and location data from the National Lightning Detection Network (NLDN), Pu et al (2020) determined the source altitude for the TGF to be from 5.4 to 6.7 km. The slow-pulse event occurs roughly 3 ms after the IBPs signaling the initiation of the downward negative leader and roughly 3 ms prior to the return stroke.…”
mentioning
confidence: 99%